Evaluation of serum cystatin c as a new marker of Renal failure in small animal medicine - shruti chhibber; Kafil Hussain; Azhar Shuaib Batoo; Muheet; Mazar Ali Shah; Sumreen Kour; Rajiv Singh (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Kidney diseases commonly affect dogs. Early diagnosis of renal impairment may be challenging even when urinalysis is used to provide additional information. Serum creatinine concentration is mainly used in the diagnosis, but it is a relatively insensitive marker of renal function. Now a days attention is paid to investigate certain molecules that will increase in serum as a result of glomerular or tubular dysfunction. These changes may be found before the increase of serum creatinine levels. Early diagnosis of reduced renal functional mass allows early therapeutic interventions which may decrease morbidity and mortality. The concentration of serum cystatin C is mainly determined by glomerular filtration, which makes cystatin C an endogenous marker of glomerular filtration rate. The serum cystatin C concentration is a better filtration marker than plasma creatinine concentration in humans. In veterinary medicine, no studies studies have shown that the serum Cystatin C concentration in dogs is better marker than the plasma Creatinine concentration. The purpose of this study is to evaluate the applicability of measuring the serum Cystatin C concentration as a marker of the glomerular filtration rate in dogs with various renal dysfunctions. From the study of renal diseases of dogs it was concluded that serum cystatin C is a better marker of renal failure than serum creatinine. A highly significant increase was observed in serum cystatin C level in renal failure cases. The overall correlation coefficient of glomerular filtration rate with the reciprocal of serum cystatin C in renal failure dogs was superior to that of the reciprocal of serum creatinine.